The Efficacy of FlexMaster’s IntroFile, PreRaCe and Gates Glidden Drills in Straight-Line Access: A CBCT Assessment - Farhad Molashahi, Narges; Sohrabi, Mahdi; Farhad Molashahi, Leila; Mehdizadeh, Mojdeh (Iranian Endodontic Journal, 2014)
Introduction: An overlooked but important part of successful root canal treatment is a straight-line access (SLA). The purpose of this in vitro study was to compare the efficacy of IntroFile and PreRaCe rotary instruments with Gates Glidden (GG) drills in gaining SLA by cone-beam computed tomography (CBCT). Methods and Materials: A total of forty five extracted mandibular first molars were selected and mounted in dental like arches. Subsequently, they were randomly classified into three groups (n=15). After preparation of a standard access cavity, orifices of the mesiobuccal canal was reached and a #10 file was inserted to explore the canals until the file tip was visible at the apex. Then, preoperative CBCT images were taken. SLA was gained in three groups; group 1, FlexMaster’s IntroFile (FM); group 2, PreRaCe (RC) and group 3, GG. Again, the first binding file at the working length (WL) was placed in the canal and postoperative CBCT images in similar positions were taken. The pre/post operative morphology of the canal was evaluated for changes. Data was analyzed using the one-way ANOVA and post-hoc Bonferroni analysis. Results: The average amount of reduction in coronal canal curvature in FM, RC and GG groups was 2.43±1.79, 3.17±2.05 and 8.7±3.45, respectively. This descending trend was statistically significant. The difference between pre/post SLA changes in FM and RC groups was significant compared to GG group, while there were no significant differences between RC and FM. Conclusion: GG drills produced extraordinary results in reducing coronal curvature of the canal and achieving SLA. They are also more effective than nickel-titanium (NiTi) rotary instruments in canals with coronal curvature.